Elevated Ferritin Levels during First Trimester Associated with GDM - Rizzo, Toni (MD Conference Express, 2014)
Gestational diabetes mellitus (GDM) can lead to short- and long-term health risks for both the mother and the infant, including increased risk of type 2 diabetes later in life. This article presents results of a retrospective study that aimed to determine whether an elevated serum ferritin level during the first trimester is associated with subsequent GDM when there is no evidence of inflammation.